1983
DOI: 10.1099/0022-1317-64-5-1025
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of a Cytomegalovirus from an American Bison Affected with Malignant Catarrhal Fever

Abstract: SUMMARYA herpesvirus isolated from several organs of an American bison affected with malignant catarrhal fever was cultured in bovine foetal spleen cells and studied by electron microscopy. The fine structural features of the mature virion and the mode of virus morphogenesis were found to be similar to herpesviruses classified in the subgroup cytomegalovirus. The capsids were granular, hexagonal in shape and contained pleomorphic cores in thin sections. Envelopment of the capsids occurred primarily by budding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…Indeed, it has been shown that BoHV-4 is able to replicate in a broad range of host species both in vivo and in vitro. In addition to cattle, isolates of BoHV-4 have been recovered from other ruminant species (7)(8)(9)(10). Sporadic isolations were also reported in lions, cats, and owl monkeys (Aotus trivirgatus; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that BoHV-4 is able to replicate in a broad range of host species both in vivo and in vitro. In addition to cattle, isolates of BoHV-4 have been recovered from other ruminant species (7)(8)(9)(10). Sporadic isolations were also reported in lions, cats, and owl monkeys (Aotus trivirgatus; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Isolates of BoHV-4 have also been recovered from other ruminant species such as American bison (Bison bison) (32), African buffalo (Syncerus caffer) (26), and sheep (36). Sporadic isolations were reported in lions, cats (9), and owl monkeys (Aotus trivirgatus) (1).…”
mentioning
confidence: 99%
“…1,2 The PCR test has been successfully applied to detect OHV2 DNA in peripheral blood leukocytes 1 and in tissues from terminal cases of SA-MCF in bison 24 and cattle. 4 Previous investigations of SA-MCF resulted in the detection of a cell-associated cytomegalovirus, 30 and retroviruses. 12,27 In the present study, cases of SA-MCF in cattle and bison were analyzed retrospectively for OHV2 and for other persistent bovine herpesviruses, retroviruses, and pestivirus.…”
mentioning
confidence: 99%